Performance and usefulness of the Hexagon rapid diagnostic test in children with asymptomatic malaria living in the Mount Cameroon region - Eyong Joan E; Kimbi Helen K; Wanji Samuel; Tendongfor Nicholas; Ndamukong Judith L (Malaria Journal, 2008)
Abstract Background Rapid and correct diagnosis of malaria is considered an important strategy in the control of the disease. However, it remains to be determined how well these tests can perform in those who harbour the parasite, but are asymptomatic, so that rapid diagnostic tests (RDTs) could be used in rapid mass surveillance in malaria control programmes. Methods Microscopic and immunochromatographic diagnosis of malaria were performed on blood samples from the hyperendemic Mount Cameroon region. Thin and thick blood films were stained with Giemsa and examined under light microscopy for malaria parasites. The RDT was performed on the blood samples for the detection of Plasmodium species. In addition, the performance characteristics of the test were determined using microscopy as gold standard. Results Results revealed 40.32% to be positive for microscopy and 34.41% to be positive for the RDT. Parasites were detected in a greater proportion of samples as the parasite density increase. Plasmodium falciparum was the predominant Plasmodium species detected in the study population either by microscopy or by the RDT. Overall, the test recorded a sensitivity and specificity of 85.33% and 95.05% respectively, and an accuracy of 91.40%. The sensitivity and specificity of the RDT increased as parasite densities increased. Conclusion The Hexagon Malaria Combi™ test showed a high sensitivity and specificity in diagnosing malaria in asymptomatic subjects and so could be suitable for use in mass surveillance programmes for the management and control of malaria.